Health Risk Assessment of Black Carbon Emission from Fossil Fuel. (Journal of Engineering Science, 2021)
Fossil fuel combustion is one of the major sources of carbonaceous emission throughout the world. In this study, two light absorbing carbonaceous aerosol namely Black carbon (BC) and Brown carbon (BrC) from fossil fuel combustion under controlled laboratory condition was reported. Four different fossil fuels; octane, petrol, diesel and kerosene was taken as samples (Four different fossil fuels; octane, petrol, diesel, and kerosene samples were collected from filling station of Nilkhet, Dhaka City. Two wavelengths Aethalometer (OT21) had been taken for systematic analysis of Black carbon and Brown carbon. BC and BrC particulates were determined in terms of density, concentration, emission and emission factor. The concentrations of Black carbon in mgm-3 for respective fuel samples were kerosene (3.83), diesel (4.59), petrol (7.94), octane (13.18) while concentrations of Brown carbon were kerosene (7.77), diesel (7.98), petrol (13.61), octane (20.46). BrC concentrations were found to be higher than those of BC for all the fuel samples. Average concentrations of Black carbon and Brown carbon were 7.38 mgm-3 and 11.46 mgm-3 respectively. Thereafter, health risk assessment for chronic exposure to Black carbon was done (estimated/ evaluated/ calculated) according to the U.S. EPA human health risk assessment protocol. Experimental results were correlated with the data given by the Exposure Factors Handbook of EPA for assessing carcinogenic and non-carcinogenic risk associated with BC. Total carcinogenic risk (CR) was found to be 3.27 for adults and 1.34 for children. While total noncarcinogenic risk i.e hazard quotient (HQ) for adults and children were 243.32 and 594.32 respectively. Both CR and HQ values crossed the safe limit given by the US EPA protocol indicating high probability of the occurrence of adverse health effects.Journal of Engineering Science 12(2), 2021, 23-28